Characterizations of chromosome aberrations, telomere dysfunction, and radiosensitivity signatures in canine cancer cell lines - Maeda, Junko, author; Kato, Takamitsu, advisor; Bedford, Joel, committee member; Bailey, Susan, committee member; Thamm, Douglas, committee member (Colorado State University. Libraries, 2015)
To view the abstract, please see the full text of the document.
Keywords: chromosome aberrations; telomere dysfunction; radiosensitivity; canine cancer cell lines